Fevered fingers; the hot breath of Kenya - Mallett, Daniel Trowbridge, 1862-
Holograph manuscript of Mallett's unpublished novel.
Publisher and author. Died 1944.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Authors; Publishers